A Novel AdpA Homologue Negatively Regulates Morphological Differentiation in Streptomyces xiamenensis 318 - Bu, Xu-Liang (Appl Environ Microbiol, 2019)
The pleiotropic transcriptional regulator AdpA positively controls morphological differentiation and regulates secondary metabolism in most Streptomyces species. Streptomyces xiamenensis 318 has a linear chromosome 5.96 Mb in size. How AdpA affects secondary metabolism and morphological differentiation in such a naturally minimized genomic background is unknown. Here, we demonstrated that AdpA(Sx), an AdpA orthologue in S. xiamenensis, negatively regulates cell growth and sporulation and bidirectionally regulates the biosynthesis of xiamenmycin and polycyclic tetramate macrolactams (PTMs) in S. xiamenensis 318. Overexpression of the adpA(Sx) gene in S. xiamenensis 318 had negative effects on morphological differentiation and resulted in reduced transcription of putative ssgA, ftsZ, ftsH, amfC, whiB, wblA1, wblA2, wblE, and a gene encoding sporulation-associated protein (sxim_29740), whereas the transcription of putative bldD and bldA genes was upregulated. Overexpression of adpA(Sx) led to significantly enhanced production of xiamenmycin but had detrimental effects on the production of PTMs. As expected, the transcriptional level of the xim gene cluster was upregulated, whereas the PTM gene cluster was downregulated. Moreover, AdpA(Sx) negatively regulated the transcription of its own gene. Electrophoretic mobility shift assays revealed that AdpA(Sx) can bind the promoter regions of structural genes of both the xim and PTM gene clusters as well as to the promoter regions of genes potentially involved in the cell growth and differentiation of S. xiamenensis 318. We report that an AdpA homologue has negative effects on morphological differentiation in S. xiamenensis 318, a finding confirmed when AdpA(Sx) was introduced into the heterologous host Streptomyces lividans TK24. IMPORTANCE AdpA is a key regulator of secondary metabolism and morphological differentiation in Streptomyces species. However, AdpA had not been reported to negatively regulate morphological differentiation. Here, we characterized the regulatory role of AdpA(Sx) in Streptomyces xiamenensis 318, which has a naturally streamlined genome. In this strain, AdpA(Sx) negatively regulated cell growth and morphological differentiation by directly controlling genes associated with these functions. AdpA(Sx) also bidirectionally controlled the biosynthesis of xiamenmycin and PTMs by directly regulating their gene clusters rather than through other regulators. Our findings provide additional evidence for the versatility of AdpA in regulating morphological differentiation and secondary metabolism in Streptomyces.